2009
DOI: 10.1007/s12262-009-0021-8
|View full text |Cite
|
Sign up to set email alerts
|

Has experience changed the scenario in laparoscopic adrenalectomy?

Abstract: Though technically difficult, with increasing experience and focused approach, laparoscopic skills in adrenalectomy improves. The spectrum of indications broadens, thus making laparoscopic interventions for vascular and large adrenal glands safe and patient friendly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
2
0
2
Order By: Relevance
“…6,26 However, the need for blood transfusion was the same in both groups. Mellon et al, 19 showed blood loss as well as the need for blood transfusion were not statistically different between both groups. According to our results, there was no statistically difference as regard intra-and postoperative complications.…”
Section: Discussionmentioning
confidence: 90%
“…6,26 However, the need for blood transfusion was the same in both groups. Mellon et al, 19 showed blood loss as well as the need for blood transfusion were not statistically different between both groups. According to our results, there was no statistically difference as regard intra-and postoperative complications.…”
Section: Discussionmentioning
confidence: 90%
“…According to our experience, the CO 2 insufflation pressure was usually between 12 cmH 2 O and 15 cmH 2 O. Studies have shown that these complications are mainly related to the different learning curves among surgeons [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Com relação às características do tumor, a cirurgia aberta tem preferência quando a lesão for especialmente grande (> 12 cm, dependendo da experiência do cirurgião) ou para o câncer adrenocortical localmente invasivo em que for necessário realizar linfadenectomia ou examinar órgãos adjacentes 1,3 . A primeira adrenalectomia videolaparoscópica foi relatada em 1992 por Gagner et al Desde então, vários estudos comparativos têm demonstrado as vantagens dessa técnica quando comparada com a cirurgia convencional por via aberta [4][5][6][7] . A adrenalectomia laparoscópica pode ser realizada utilizando um acesso transabdominal ou retroperitoneal; porém, o primeiro é preferível, principalmente para tumores grandes 1,8 .…”
unclassified
“…As complicações intraoperatórias mais descritas na literatura são: sangramento, lesões de outros órgãos e estruturas anatômicas, e pneumotórax. As pós-operatórias são: abscesso retroperitoneal, pneumonia e arritmias cardíacas 5,12,13 .…”
unclassified